Contemporary studies on relationships, health, and wellness - Theiss, Jennifer; Greene, Kathryn (Cambridge : Cambridge University Press, 2019)
"This volume showcases studies from various disciplines that are on the leading edge of research exploring the interdependence between health and relationships, including scholarship from the fields of communication, counseling, health services, human development and family studies, public health, and psychology. The research included in this volume highlights several relationship processes that are instrumental in the maintenance of health and the management of illness, including interpersonal influence, information management, uncertainty, social support, and communication. Although the existing health literature is rich with knowledge about individual and ecological factors that are influential in promoting certain health behaviors, relationship scholars have much to contribute in terms of documenting the interpersonal dynamics that are involved in experiences of health and illness"--Provided by publisher
Part I. Interpersonal influence in health and relationships -- Differences in perceptions of spousal influence and family communication in cancer risk-reducing behaviors / Wendy C. Birmingham, Maija Reblin -- Stigma, heteronormative passing with health care providers, and partner health involvement in male same-sex couples / Stephen M. Haas -- Let's take a walk : relationship maintenance, health communication in romantic relationships / Tricia J. Burke -- Part II. Information management in health and relationships -- Health-related issues that individuals with type 2 diabetes avoid discussing with their romantic partner / John Leustek, Jennifer A. Theiss -- Closeness, recipient response, and interaction effectiveness : an application of the actor-partner interdependence model in mental health disclosures / Maria K. Venetis, Patricia E. Gettings, Skye Chernichky-Karcher -- From the drawing board to the kitchen table : an analysis of parental messages concerning nutrition, physical activity, and weight / Emily Scheinfeld, Erin Nelson, Brittani Crook -- Part III. Uncertainty in health and relationships -- We have been robbed of the life we planned : relational rurbulence and experiences of Alzheimer's disease / Danielle Catona -- Communication as a source of misunderstanding and a resource for responding to the stress of parental caregiving / Teresa Keeler -- Examining uncertainty and interference with cardiology patients : applying a relational turbulence perspective in health contexts / Amanda Carpenter, Kathryn Greene, Maria G. Checton, Danielle Catona -- Uncertainty management in bereavement : parent and child uncertainty sources and management strategies / Brandi N. Frisby, Jacob M. Matig, Christina J. Harris -- Part IV. Support and caregiving in health and relationships -- Family reactions to partner stress and depression in same-sex couples : a dyadic examination of the moderating effects of dyadic coping / Chun Tao, Ashley K. Randall, Casey J. Totenhagen -- I Just want my wife, my life back : men's experiences of stress, social support during their partner's postpartum depression / Keli Steuber-Fazio, Keelin Moran, Caitlin McNair, Erica Cogland -- Communication skills (comskil) training for oncology nurses to improve patient-centered care / Smita C. Banerjee, Ruth Manna, Patricia A. Parker -- Part V. Communication patterns in health and relationships -- Alcoholic and nonalcoholic parents' orientations toward conformity and conversation as predictors of attachment and psychological well-being for adult children of alcoholics / Marie C. Haverfield, Jennifer A. Theiss -- Alzheimer's caregiver distress in adulthood : the role of time invested in caregiving and family verbal aggression in childhood / Lindsay Susan Aloia, Anne M. Stone -- Depression and sexual intimacy : layered challenges and communication strategies / Amy L. Delaney -- Epilogue : The important role of relationship research in promoting healthy individuals and relationships / Jennifer A. Theiss, Kathryn Greene.
Print version record.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Health attitudes; Interpersonal relations; Health; Attitude to Health; Interpersonal Relations; Social Support; Health; Attitudes à l'égard de la santé.; Santé.; health; HEALTH & FITNESS -- Healthy Living; HEALTH & FITNESS -- Holism; HEALTH & FITNESS -- Reference; MEDICAL -- Preventive Medicine; Health attitudes; Interpersonal relations